Biomechanical Changes in the Sclera of Monkey Eyes Exposed to Chronic IOP Elevations - Girard, Michael J. A.; Suh, J. -K. Francis; Bottlang, Michael; Burgoyne, Claude F.; Downs, J. Crawford (ASSOC RESEARCH VISION OPHTHALMOLOGY INC, 2011)
PURPOSE. To characterize scleral biomechanics in both eyes of eight monkeys in which chronic intraocular pressure (IOP) elevation was induced in one eye. METHODS. Each posterior sclera was mounted on a pressurization apparatus, IOP was elevated from 5 to 45 mm Hg while the 3D displacements of the scleral surface were measured by speckle interferometry. Finite element (FE) models of each scleral shell were constructed that incorporated stretch-induced stiffening and multidirectionality of the collagen fibers. FE model predictions were then iteratively matched to experimental displacements to extract unique sets of scleral biomechanical properties. RESULTS. For all eyes, the posterior sclera exhibited inhomogeneous, anisotropic, nonlinear biomechanical behavior. Biomechanical changes caused by chronic IOP elevation were complex and specific to each subject. Specifically: (1) Glaucomatous eyes in which the contralateral normal eyes displayed large modulus or thickness were less prone to biomechanical changes; (2) glaucomatous scleral modulus associated with an IOP of 10 mm Hg decreased (when compared with that of the contralateral normal) after minimal chronic IOP elevation; (3) glaucomatous scleral modulus associated with IOPs of 30 and 45 mm Hg increased (when compared with that of the contralateral normal) after moderate IOP elevation; and (4) FE-based estimates of collagen fiber orientation demonstrated no change in the glaucomatous eyes. CONCLUSIONS. Significant stiffening of the sclera follows exposure to moderate IOP elevations in most eyes. Scleral hyper-compliance may precede stiffening or be a unique response to minimal chronic IOP elevation in some eyes. These biomechanical changes are likely to be the result of scleral extracellular matrix remodeling. (Invest Ophthalmol Vis Sci. 2011;52:5656-5669) DOI:10.1167/iovs.10-6927
Keywords: OPTIC-NERVE HEAD; LAMINA-CRIBROSA; CONNECTIVE-TISSUE; MECHANICAL-PROPERTIES; 3-D HISTOMORPHOMETRY; PERIPAPILLARY SCLERA; WALL MECHANICS; GLAUCOMA; STRAIN; DEFORMATION